2002
DOI: 10.1046/j.1524-4741.2002.08203.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and Body Mass Index May Increase the Chance of Failure in Sentinel Lymph Node Biopsy for Women with Breast Cancer

Abstract: Age and body mass index (BMI) have been shown to correlate with an increased incidence of failure in identifying a sentinel lymph node (SLN). Mapping senior, overweight adults is common; therefore, the relationship of patient age and BMI on SLN biopsy success is essential. This study examines the mapping failures as they relate to age and BMI. From April 1994 to May 1999, patients underwent an injection of radiocolloid (450 mci) and blue dye (5 cc) prior to SLN biopsy. SLN biopsy failure was defined as lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 15 publications
2
67
0
2
Order By: Relevance
“…Thus, increased age is inversely correlated with the ability to visualize axillary hotspots and internal mammary hotspots. 13,[25][26][27][28][29] Likewise, our study showed that the mean age of patients with initial scan failure was significantly higher when compared with patients with a successful initial lymphoscintigraphy (65.8 years versus 58.5 years, p \ 0.0001).…”
Section: Increased Agementioning
confidence: 96%
See 1 more Smart Citation
“…Thus, increased age is inversely correlated with the ability to visualize axillary hotspots and internal mammary hotspots. 13,[25][26][27][28][29] Likewise, our study showed that the mean age of patients with initial scan failure was significantly higher when compared with patients with a successful initial lymphoscintigraphy (65.8 years versus 58.5 years, p \ 0.0001).…”
Section: Increased Agementioning
confidence: 96%
“…26,27,30 As is true for increased age, patients with high BMI might have sparse lymphatic capillaries and more fatty tissue in their breast parenchyma.…”
Section: Body Mass Index (Bmi)mentioning
confidence: 99%
“…Studies have shown factors related to inability to identify the SLN, most important of which includes the surgeon's volume [27,28]. Patient factors shown to increase the likelihood of not finding the SLN include increasing age and body mass index [29]. The accuracy of SLN mapping to predict the status of the axillary basin has been born out in many studies.…”
Section: Breastmentioning
confidence: 99%
“…Reasons for false negative results are attributed to changes in surgical personnel, difficult lymph node location and absence of a thorough histological study [90] . Factors militating against sentinel node identification are increasing age and body mass index [91] . A review of ten large observational studies revealed just ten axillary recurrences in 2664 patients (0.4%) who did not undergo ALND following negative SLN biopsy [43] .…”
Section: False Negative Ratementioning
confidence: 99%